2014
DOI: 10.1016/j.rmed.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CPAP treatment on plasma high sensitivity troponin levels in patients with obstructive sleep apnea

Abstract: This study shows that the percentage of subjects with detectable hs-cTnT is associated with the presence of OSA. It also evidences that treatment with CPAP is followed by a rise in hs-cTnT concentrations. It is reasonable to suggest that CPAP therapy might induce a potential degree of cardiac stress, resulting in deleterious consequences for the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
(11 reference statements)
2
17
0
Order By: Relevance
“…In an interesting finding, Barcelo and colleagues found an unanticipated increase in hs-cTnT levels after treatment with PAP for 12 months, compared with controls without OSA [130]. Subjective assessment of PAP adherence was not explicitly described in this study, and as such this may impact interpretation of the results.…”
Section: The Role Of Pap Therapy and Troponinsmentioning
confidence: 68%
See 4 more Smart Citations
“…In an interesting finding, Barcelo and colleagues found an unanticipated increase in hs-cTnT levels after treatment with PAP for 12 months, compared with controls without OSA [130]. Subjective assessment of PAP adherence was not explicitly described in this study, and as such this may impact interpretation of the results.…”
Section: The Role Of Pap Therapy and Troponinsmentioning
confidence: 68%
“…Current evidence (see Table 3) primarily suggests that PAP adherence does not affect cTns [133][134][135] in the overall OSA population. However, one study showed a change in the levels of cTn, an increase in hs-cTnT levels with CPAP use [130].…”
Section: The Role Of Pap Therapy and Troponinsmentioning
confidence: 99%
See 3 more Smart Citations